GERMINATION-GROWTH PROTOCORMS OF PAPILIONANTHE HOOKERIANA ORCHIDS FROM BANGKA ON BASAL MEDIA, ORGANIC ADENDA, AND PLANT GROWTH REGULATOR - Zasari, Maera (Jurnal Agrotek Tropika, 2025)
The pencil orchid (Papilionanthe hookeriana) from Bangka is starting to become endangered. The preservation of the pencil orchid from Bangka will be made easier if orchid seeds are available in large quantities. In vitro germination is an effective method for producing Papilionanthe hookeriana orchid seeds from Bangka. The research was carried out at the Plant Tissue Culture Laboratory, Faculty of Agriculture, Fisheries and Biology, Bangka Belitung University, from May to October 2023. The research used a completely randomized factorial design. Basic media ½ MS and Growmore combined with pineapple extract 200 g/l, carrot extract 200 g/l, tomato extract g/l, coconut water 150 ml/l) for seed germination. The same combination treatment of basic media and organic additives added 2 mg /L NAA or BA for PLBs growth assay. Each treatment consisted of 3 (three) bottles and was repeated 3 times. Research has found that ½ MS media is the best for seed germination; ½ MS media plus the best tomato or carrot extract produces the best number of germinating seeds; the best growth of PLBs was obtained on Growmore media; The best growth of PLBs was obtained on Growmore media plus tomato extract and NAA.